Tunable colloid trajectories in nematic liquid crystals near wavy walls - Yimin Luo (Nature Portfolio, 2018)
Nematic liquid crystals have a rich energy landscape which can define elastic fields to guide colloidal assembly. Here the authors show controllable trapping of colloidal particles by placing them in a system with wavy walls which are exploited to obtain stable, metastable and unstable equilibria.